Analisis Hasil Belajar Matematika Siswa Ditinjau dari Intellegence Quotient - Ulvy Andari; Dewi Sri Lestari (JUMAT: Jurnal Matematika, 2023)
This study aims to describe the relationship between mathematics learning outcomes in terms of intelligence quotient (IQ). The subjects of this study were selected based on test results and predetermined categories. The data collection technique used consisted of two tests, namely a math test to find out learning outcomes and an IQ test to measure students' IQ levels. The results showed that the level of the students' IQ affected the learning outcomes obtained. In addition, the results of the interviews show that there are several factors that become obstacles and are often faced by students in learning, including internal and external factors. Internal factors are feeling lazy, not liking math lessons, lack of understanding of the material, and lack of time to practice working on practice questions. The external factors in this study were the unconducive classroom atmosphere which made it difficult for students to focus, the teacher's delivery was difficult to understand, and the lack of motivation and encouragement from the family, such as the presence of parents in student learning.